Degradation pathways of 1-methylphenanthrene in bacterial Sphingobium sp. MP9-4 isolated from petroleum-contaminated soil. Issue 2 (30th January 2017) - Zhong, Jianan; Luo, Lijuan; Chen, Baowei; Sha, Sha; Qing, Qing; Tam, Nora F.Y.; Zhang, Yong; Luan, Tiangang
Abstract: Alkylated polycyclic aromatic hydrocarbons (PAHs) are abundant in petroleum, and alkylated phenanthrenes are considered as the primary PAHs during some oil spill events. Bacterial strain of Sphingobium sp. MP9-4, isolated from petroleum-contaminated soil, was efficient to degrade 1-methylphenanthrene (1-MP). A detailed metabolism map of 1-MP in this strain was delineated based on analysis of metabolites with gas chromatograph–mass spectrometer (GC–MS). 1-MP was initially oxidized via two different biochemical strategies, including benzene ring and methyl-group attacks. Benzene ring attack was initiated with dioxygenation of the non-methylated aromatic ring via similar degradation pathways of phenanthrene (PHE) by bacteria. For methyl-group attack, mono oxygenase system was involved and more diverse enzymes were needed than that of PHE degradation. This study enhances the understanding of the metabolic pathways of alkylated PAHs and shows the significant potential of Sphingobium sp. MP9-4 for the bioremediation of alkylated PAHs contaminated environments. Highlights: Bacterial strain of Sphingobium sp. MP9-4 was isolated to degrade alkylated PAHs. Detailed metabolism map of 1-methylphenanthrene (1-MP) was delineated. 1-MP was initially oxidized via benzene ring and methyl-group attacks. Monooxygenase and dioxygenase systems were involved in 1-MP degradation.